2022
DOI: 10.1038/s41377-021-00704-5
|View full text |Cite
|
Sign up to set email alerts
|

Light amplified oxidative stress in tumor microenvironment by carbonized hemin nanoparticles for boosting photodynamic anticancer therapy

Abstract: Photodynamic therapy (PDT), which utilizes light excite photosensitizers (PSs) to generate reactive oxygen species (ROS) and consequently ablate cancer cells or diseased tissue, has attracted a great deal of attention in the last decades due to its unique advantages. However, the advancement of PDT is restricted by the inherent characteristics of PS and tumor microenvironment (TME). It is urgent to explore high-performance PSs with TME regulation capability and subsequently improve the therapeutic outcomes. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…When compared to traditional PDT, P-CHNPs-based PDT has been shown to reduce tumor size in xenografted mice. Interestingly, the study showed that P-CHNPs are biocompatible and did not affect hematological and biochemical markers or vital organs (Lin et al., 2022 ). During PDT, Fe 3 O 4 NPs can induce the Fenton reaction in tumor cells, converting hydrogen peroxide to hydroxyl radicals.…”
Section: Application Of Nps In Cancer Therapymentioning
confidence: 99%
“…When compared to traditional PDT, P-CHNPs-based PDT has been shown to reduce tumor size in xenografted mice. Interestingly, the study showed that P-CHNPs are biocompatible and did not affect hematological and biochemical markers or vital organs (Lin et al., 2022 ). During PDT, Fe 3 O 4 NPs can induce the Fenton reaction in tumor cells, converting hydrogen peroxide to hydroxyl radicals.…”
Section: Application Of Nps In Cancer Therapymentioning
confidence: 99%
“…In this issue, Shramova et al from the Russian Academy of Sciences developed genetically encoded bioluminescence resonance energy transfer (BRET)-activated photodynamic therapy toward a self-glowing, deep-tissue “photodynamic” therapy without any external light source 16 . With polymer-encapsulated carbonized hemin nanoparticles as photosensitizers, Lin et al from Shanghai Jiao-tong University demonstrated superior in vitro and in vivo PDT effects through improved ROS generation efficiency, hypoxia relief, and glutathione depletion 17 .…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…As another emerging ROS-triggered therapeutic modality, CDT, which employs a catalytic reaction through Fenton or Fenton-like agents, can efficiently convert the excessive H 2 O 2 in the TME into • OH in situ independent of the tumor hypoxia nature. Given its high selectivity, low invasiveness, and independence on O 2 or external energy, emerging CDT has been considered a compelling ROS-based therapy. However, the efficacy of CDT is usually restricted by the unsatisfactory catalytic efficiency of multivalent metal ion-based (such as Fe 2+ /Fe 3+ , Mn 2+ /Mn 4+ , and Cu + /Cu 2+ ) nanoplatforms. It has been demonstrated that the elevated local temperature at the tumor site can accelerate the catalytic rate and effectively enhance the efficiency of the Fenton reaction, thus amplifying the CDT effect. , Ideally, multi-functionalities, including photosensitizer delivery, O 2 self-supplying, photothermal conversion, and • OH production by H 2 O 2 catalysis, should be integrated into a unitary agent so that the ROS-mediated cancer therapy could be distinctly enhanced. Therefore, integrating CDT with phototherapy (PDT and PTT) would circumvent the inherent shortcomings and improve the low anticancer efficacy of monotherapy. However, developing a simplified system that synergistically combines two or more therapeutic modalities and synchronously relieves TME hypoxia remains an unsettled challenge …”
Section: Introductionmentioning
confidence: 99%
“…For hypoxia alleviation, the naturally occurring catalase is commonly used to supply O 2 by in situ catalyzing the overly existing H 2 O 2 at the tumor site . However, the high cost, easy deactivation, and degradation in complex biological environments seriously impede the widespread popularity and applications of natural enzymes. , Over the past decade, artificial enzyme-like nanomaterials, known as “nanozymes”, have been developed as prospective alternatives for natural enzymes due to their low cost, high stability, and facile synthesis. , Nanozymes not only inherit the catalytic activities of natural enzymes to regulate biochemical reactions but also retain the features of nanomaterials, making them promising platforms for versatile applications. , Up to now, diverse nanozymes, such as Pt, Au, Pd, Au 2 Pt, Fe 3 O 4 , and CeO 2 , have been explored to mimic natural enzymes for colorimetric detection, antibiosis, and therapy. Taking advantage of the unique TME characteristics, such as mild acidity, hypoxia, and excessive H 2 O 2 , pH- and H 2 O 2 -responsive nanozymes have attracted considerable interest and exhibited great promise for cancer catalytic therapy. , As previously reported, peroxidase (POD) mimetics could supply highly toxic ROS by decomposing H 2 O 2 under acidic conditions, while catalase (CAT) mimetics could react with H 2 O 2 to produce O 2 under neutral conditions. , Therefore, a nanoplatform with both POD- and CAT-like activities is promising for effective anticancer therapy, yet it remains challenging to develop high-performance nanomaterials with multi-enzymatic activities for multifunctional nanotheranostic applications.…”
Section: Introductionmentioning
confidence: 99%